2013
DOI: 10.1016/j.bbi.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Aging leads to prolonged duration of inflammation-induced depression-like behavior caused by Bacillus Calmette-Guérin

Abstract: Geriatric depression is a costly health issue, but little is known about its physiological underpinnings. Systemic inflammation sensitizes the innate immune system of aged animals and humans, but it is unknown if chronic, low-grade infections affect the duration of depressive-like behaviors. In this report, we infected adult (4–6 months) and aged (20–24 months) Balb/c mice with an attenuated strain of Mycobacterium bovis, Bacillus Calmette-Guérin (BCG), to induce a chronic infection. We then measured depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…In line with clinical findings, preclinical studies performed in rodents treated with an immune challenge have documented associations between emotional/cognitive alterations and both peripheral and brain IDO activation (Andre et al, 2008;Corona et al, 2013;Frenois et al, 2007;Gibney et al, 2013;Lawson et al, 2013;Lestage et al, 2002;Moreau et al, 2005Moreau et al, , 2008Salazar et al, 2012;Xie et al, 2014). In addition, aged mice or mice with constitutive microglial overactivation display, upon immune challenge, sustained cytokine production together with protracted brain IDO expression and depressive-like behavior (Corona et al, 2010;Godbout et al, 2008;Kelley et al, 2013). More importantly, pharmacological or genetic inhibition of IDO prevents the development of depressive-/anxiety-like behaviors and cognitive impairments (Barichello et al, 2013;Henry et al, 2009;O'Connor et al, 2009a;O'Connor et al, 2009b;O'Connor et al, 2009c;Salazar et al, 2012;Xie et al, 2014).…”
Section: Neuropsychiatric Effects Of Inflammation: Evidence and Mechamentioning
confidence: 61%
“…In line with clinical findings, preclinical studies performed in rodents treated with an immune challenge have documented associations between emotional/cognitive alterations and both peripheral and brain IDO activation (Andre et al, 2008;Corona et al, 2013;Frenois et al, 2007;Gibney et al, 2013;Lawson et al, 2013;Lestage et al, 2002;Moreau et al, 2005Moreau et al, , 2008Salazar et al, 2012;Xie et al, 2014). In addition, aged mice or mice with constitutive microglial overactivation display, upon immune challenge, sustained cytokine production together with protracted brain IDO expression and depressive-like behavior (Corona et al, 2010;Godbout et al, 2008;Kelley et al, 2013). More importantly, pharmacological or genetic inhibition of IDO prevents the development of depressive-/anxiety-like behaviors and cognitive impairments (Barichello et al, 2013;Henry et al, 2009;O'Connor et al, 2009a;O'Connor et al, 2009b;O'Connor et al, 2009c;Salazar et al, 2012;Xie et al, 2014).…”
Section: Neuropsychiatric Effects Of Inflammation: Evidence and Mechamentioning
confidence: 61%
“…These results are in agreement with previous studies using a number of mice strains and genotypes where BCG-challenged mice exhibited a drop in weight during the first 2 days post-challenge followed by a weight gain (Moreau et al, 2008; O’Connor et al, 2009; Platt et al, 2013; Painsipp et al, 2013; Vijaya Kumar et al, 2014). The speed of recovery of body weight varies with study and strain and meanwhile in some studies body weight does not differ among BCG-treated and BCG0 mice by Day 6 (Pratt et al, 2013; Painsipp et al, 2013), in other studies weight recovery is detected after Day 7 (Moreau et al, 2008; Kelley et al, 2013; Vijaya Kumar et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported associations between BCG-treatment and sickness and depression-like behaviors in mice (Moreau et al, 2008; O’Connor et al, 2009; Kelley et al, 2013; Painsipp et al, 2013; Platt et al, 2013; Vijaya Kumar et al, 2014). In these studies, behavioral indicators were analyzed separately.…”
Section: Introductionmentioning
confidence: 99%
“…These include (a) major contextual changes and stressors (e.g., retirement, disability, role loss; Rosow, 1973); (b) the loss of loved ones (e.g., Bruce et al, 1990; Onrust & Cuijpers, 2006); and (c) increased incidence of inflammation-triggering injury and disease (Alexopoulos & Morimoto, 2011). Comparative studies have found that older animals show exaggerated and prolonged sickness behavior in response to infection (e.g., Huang et al, 2008; Kelley et al, 2013) and human studies have found upregulated inflammatory activity with aging (Bruunsgaard, Pedersen, & Pedersen, 2001)—the degree of which correlates with depression (Baune et al, 2012). …”
Section: Individual Gender and Cultural Differences In Interoceptionmentioning
confidence: 99%